STUDY OF NUTRIENT CONTENT (NITROGEN ELEMENT) IN Kappaphycus alvarezii THALLUS IN RELATION TO FILAMENTOUS ALGAE ATTACHMENT IN THE BONE-BONE COASTAL WATERS, BAUBAU CITY - Adriyan Adriyan; Ma'ruf Kasim; Dedy Oetama (Universitas Mataram, 2026)
This study aimed to determine the nitrogen content in the thallus of K. alvarezii in relation to filamentous algae attachment. The research location was determined using the purposive sampling method. This study used a horizontal net (horinet) as a cultivation tool. Sampling of K. alvarezii thallus was conducted over 35 days with a 7-day interval. A total of 20 thallus were collected during the study, consisting of 10 thallus with attached filamentous algae and 10 thallus without attached filamentous algae. The nitrogen content in the thallus was calculated using the Kjeldahl method, which involves three main stages: digestion, distillation, and titration. The results showed that the types of attached filamentous algae included one species from the class Chlorophyta, namely Chaetomorpha crassa, and one species from the class Rhodophyta, namely Neosiphonia apiculata. The highest average nitrogen content in the thallus when filamentous algae were attached was 1.121%, and the lowest was 0.863%. In contrast, in thallus without attached filamentous algae, the highest average nitrogen content was 1.274%, and the lowest was 0.942%. The results of the one-way ANOVA test analysis indicated no significant difference in nitrogen content between thallus with and without attached filamentous algae.